ASSESSMENT OF THE STRESS-STRAIGHTENING STATE OF SURFACES WITH COMPOSITE COATINGS FORMED BY THE ELECTRO-SPIRCULATION DOPING METHOD - Shamrai, Vitaliy (Problems of Friction and Wear, 2025)
The results of the assessment of the stress-strain state of surfaces with composite coatings formed by the method of electric spark alloying are presented, which made it possible to choose the optimal variant of the surface design, the coating application process modes and the composition of the composite material. The parameters of electrospark composite coatings were determined by the stressed-deformed state of the composition "reinforcing surface - coating". Modeling of the stressed-deformed state of the composition "reinforcing surface - coating" was carried out by the method of finite element analysis in the licensed software package MSC VisualNastran for Windows 2003. The conducted studies of composite electric spark coatings of variable continuity showed that coatings with a continuity of 70…90% have much lower microstresses than coatings applied in a continuous layer. The conducted studies showed that by changing the continuity and thickness of the coating, as well as by selecting a range of materials according to their physical and mechanical characteristics, it is possible to minimize the stress-strain state of the surfaces to be strengthened and control it. Variable continuity electrospark composite coatings with an optimal thickness of 200 microns allow solving the main issue that arises during the formation of superhard strengthening surface layers - to form a coating that will not be characterized by brittleness. Variable continuity electrospark coatings provide limited stress growth and the process of crack formation, which significantly increases its wear resistance, strength and durability, eliminating cohesive cracking and adhesive delamination of the coating.